The effect of vehicle on skin absorption of Mg2+ and Ca2+ from thermal spring water. (13th April 2020) - Tarnowska, M.; Briançon, S.; Resende de Azevedo, J.; Chevalier, Y.; Arquier, D.; Barratier, C.; Bolzinger, M.‐A.
Abstract: Objective: Thermal spring waters (TSW) are commonly used as active ingredients in cosmetics. Their biological activities directly depend on the ionic composition of the spring. However, in order to exhibit beneficial properties, the minerals need to reach viable skin layers. The present study addresses the incorporation of marketed TSW in model cosmetic formulations and the impact of the formulation on skin absorption of magnesium and calcium ions that are known to improve skin barrier function. Methods: Marketed TSW was introduced into five formulations. Liposomes were prepared using saturated or unsaturated phospholipids mixed with cholesterol by the thin layer evaporation technique. Emulsions water‐in‐oil (W/O), oil‐in‐water (O/W) or double: water‐in‐oil‐in‐water (W/O/W) were prepared by high‐shear mixing. Skin absorption of Mg 2+ and Ca 2+ from those formulations was studied in vitro using static Franz diffusion cells under infinite dose condition and under occlusion of the apparatus. Results: Mg 2+ and Ca 2+ penetrate skin samples from TSW. Encapsulating TSW into double emulsion (TSW/O/W) increased skin absorption of both cations of interest and kept the Ca 2+ /Mg 2+ ratio equal to that of TSW in each skin layer. The dermal absorption of Mg 2+ from the double emulsion departs from both single emulsions. Application of liposome suspension improved the skin absorption of Ca 2+ while keeping constant that of Mg 2+, leading to unbalanced Ca 2+ /Mg 2+ ratio inside skin. Conclusion: The beneficial effects of TSW are not only due to their action on the skin surface. Their active components, especially Ca 2+ and Mg 2+ cations, reach viable skin layers in a formulation‐dependent manner. The distribution of ions inside skin depends on the type of formulation. Graphical Abstract: Skin absorption of cations from Thermal Spring Water based formulations. Résumé: Objectifs: Les eaux thermales sont couramment utilisées comme substances actives dans les formulations cosmétiques. Leurs activités biologiques dépendent directement de leur composition en ions. L'action des ions s'exerce à différents niveaux dans la peau, mais bien souvent dans les couches profondes, au‐delà du stratum corneum, qu'ils doivent donc atteindre. L'objectif de cet article est d'étudier l'absorption des ions magnésium et calcium, reconnus pour leur effet bénéfique sur la fonction barrière de la peau, depuis différentes formes galéniques formulées avec une eau thermale. Methodes: Une eau thermale commerciale a été utilisée comme phase aqueuse dans 5 formulations différentes : des liposomes formulés avec des phospholipides saturés et insaturés et du cholestérol ; des émulsions de différents sens, eau thermale/huile (TSW/O) et huile/eau thermale (O/TSW) ; une émulsion multiple eau thermale/huile/eau (TSW/O/W). L'absorption cutanée du calcium et du magnésium a été étudiée depuis ces différentes formulations, en utilisant la méthode des cellules de Franz, en dose infinie, et en fermant les cellules pour prévenir toute évaporation. Resultats: Les ions magnésium et calcium pénètrent dans la peau depuis l'eau thermale, utilisée comme contrôle. L'encapsulation de l'eau thermale dans les gouttelettes internes de l'émulsion double (TSW/O/W) permet de promouvoir la pénétration des deux ions d'intérêt dans chaque couche de la peau tout en respectant le rapport Ca 2+ /Mg 2+ obtenu avec l'eau thermale, contrairement aux émulsions simples. Les liposomes augmentent la pénétration cutanée des ions calcium, tandis que celle des ions magnésium reste constante, ce qui conduit à des rapports Ca 2+ /Mg 2+ élevés dans la peau. Conclusion: Les effets thérapeutiques des eaux thermales ne sont pas seulement dus à une action de surface. Les ions comme le calcium et le magnésium pénètrent dans la peau et exercent une action en profondeur qui dépend de la formulation dans laquelle ils sont formulés. En effet, leur distribution ions dépend de la formulation qui les contient.